PENGARUH PINJAMAN DANA DARI BADAN USAHA MILIK DESA (BUMDes) USAHA MULYA TERHADAP PENINGKATAN PENDAPATAN MASYARAKAT DI DESA TALANG MULYA KECAMATAN BATANG CENAKU KABUPATEN INDRAGIRI HULU - Peni Haryanti; Sakdanur Nas; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research was conducted to examine the effect of loan funds from village-owned enterprises (Bumdes) Mulya business on increasing community income in Talang Mulya Village, Batang Cenaku District, Indragiri Hulu Regency. The population in this study were 121 members who were members in 2018-2019. From this population, 67 members were sampled. While the analysis technique uses hypothesis testing with different tests (paired sample t-test) and simple linear regression. After analyzing the data for hypothesis testing, the significance value of the paired sample t-test shows that it is 0.000 <0.05 and it can be said that there is a significant difference in income between before making a loan and after making a loan at BUMDes Usaha Mulya. Whereas for the regression coefficient X of 0.118, it means that if the loan fund (X) increases by one unit, then the income will increase by 0.118 or 11.8%. Based on the results of the study, it was found that the Loan Fund from the Village-Owned Enterprise (Bumdes) Mulya Business had an effect on the Increase of Community Income in Talang Mulya Village, Batang Cenaku District, Indragiri Hulu Regency. Key words: Loan funds, increased community income